Detailed design of product oriented manufacturing systems - Silva, Sílvio Carmo (2006)
This paper describes a procedure for the detailed and repetitive design of manufacturing systems within an approach of constantly fitting production system configuration to the varying production needs of products and, therefore, designing Product Oriented Manufacturing Systems – POMS. The detailed design procedure depart from a set of conceptual manufacturing cell configurations and develops from there, through conceptual cell and workstation instantiation, with basis on available methods, the required manufacturing system and control mechanisms for a product or a family of similar products.